(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
On this paper is studied the stability and control of a Rotor Airplane, more specifically a MAV (Micro Air Vehicle) and how works the dynamics of flight of this unusual configuration of aircraft. It’s discussed the impact of the gyroscopic effect on stability (mainly lateral and directional stability) and was found the best feasible configuration of the stability surface, but the project of the stabilizers was limited to lifting surfaces that use airfoil sections, the possibility of a very unconventional stabilizer like other rotating cylinders or a very complex geometry wasn’t tested. The principal motivation of this study is that are few references and studies about the stability and control of this type of aircraft, and knowing that the use of rotating cylinder instead of a wing makes great modifications on the dynamic system, it’s very important to know how the system works in order to certify the MAV can complete its mission.